Knockdown of NLRP3 alleviates high glucose or TGFB1-induced EMT in human renal tubular cells. (October 2018) - Song, Shan; Qiu, Duojun; Luo, Fengwei; Wei, Jinying; Wu, Ming; Wu, Haijiang; Du, Chunyang; Du, Yunxia; Ren, Yunzhuo; Chen, Nan; Duan, Huijun; Shi, Yonghong
Abstract : Tubular injury is one of the crucial determinants of progressive renal failure in diabetic nephropathy (DN), while epithelial-to-mesenchymal transition (EMT) of tubular cells contributes to the accumulation of matrix protein in the diabetic kidney. Activation of the nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome leads to the maturation of interleukin (IL)-1B and is involved in the pathogenic mechanisms of diabetes. In this study, we explored the role of NLRP3 inflammasome on high glucose (HG) or transforming growth factor-B1 (TGFB1)-induced EMT in HK-2 cells. We evaluated EMT through the expression of α-smooth muscle actin (α-SMA) and E-cadherin as well as the induction of a myofibroblastic phenotype. Reactive oxygen species (ROS) was observed using the confocal microscopy. HG was shown to induce EMT at 48 h, which was blocked by NLRP3 silencing or antioxidant N-acetyl-L-cysteine (NAC). We found that NLRP3 interference could inhibit HG-induced ROS. Knockdown of NLRP3 could prevent HG-induced EMT by inhibiting the phosphorylation of SMAD3, P38 MAPK and ERK1/2. In addition, P38 MAPK and ERK1/2 might be involved in HG-induced NLRP3 inflammasome activation. Besides, TGFB1 induced the activation of NLRP3 inflammasome and the generation of ROS, which were blocked by NLRP3 interference or NAC. Tubular cells exposed to TGFB1 also underwent EMT, and this could be inhibited by NLRP3 shRNA or NAC. These results indicated that knockdown of NLRP3 antagonized HG-induced EMT by inhibiting ROS production, phosphorylation of SMAD3, P38MAPK and ERK1/2, highlighting NLRP3 as a potential therapy target for diabetic nephropathy.